The Effect of Group Counseling Using Self-Management Techniques on the Tendency of Nomophobia among Students of SMK Swasta PAB 8 Sampali in the Academic Year 2024/2025 - Suci, Fitri Cahaya; Nasution, Nani Barorah (Sean Institute, 2025)
This study aims to determine the effect of group counseling using self-management techniques on the tendency of nomophobia among tenth-grade students of SMK Swasta PAB 8 Sampali in the academic year 2024/2025. The type of research used is a quasi-experimental design with a one-group pre-test and post-test design. The study was conducted from May to July 2025. The subjects of the research were eight tenth-grade TBSM students of SMK Swasta PAB 8 Sampali, selected using a purposive sampling technique. The data were collected through a nomophobia questionnaire consisting of 31 valid and reliable statements. The data were analyzed using the Wilcoxon test. The results of the analysis showed that the Asymp. Sig (2-tailed) value was 0.011, which is ≤ 0.05. Therefore, H₀ is rejected and Hₐ is accepted. The mean pre-test score was 109.00, while the mean post-test score was 61.25. This indicates that the tendency of nomophobia decreased after receiving group counseling using self-management techniques, with a change interval of 43.80%. These findings demonstrate that group counseling using self-management techniques has a significant effect on reducing the tendency of nomophobia among students of SMK Swasta PAB 8 Sampali in the academic year 2024/2025, thus the hypothesis is accepted.